Electrosynthesis and Characterization of Superparamagnetic Organic-Inorganic Nanocomposite Films - Cao, Jun (My University, 2008)
New electrochemical methods were developed to fabricate superparamagnetic organic-inorganic nanocomposites. The methods were based on the electrosynthesis of (gamma)Fe2O3, Mn3O4 and NiFe2O4 in situ in a polymer matrix. Various composite materials were developed using new electrochemical strategies, which were based on the use of strong and weak polyelectrolytes and polymer-metal ion complexes. The deposited films were studied by XRD, TG, DTA, SEM and AFM. The results show that cathodic deposits with thickness of several microns can be obtained on various conductive substrates. The results reveal that the weight percentage of inorganic phase in the deposits reduced with the increase of the polymer concentration in the electrochemical bath solution. The particle size distribution was measured by HRTEM and evaluated by theoretical models interpreting the magnetic measurement data. The two methods are in good agreement with each other. The results show that the average particle sizes of Mn3O4 and (gamma)-Fe2O3 can be adjusted by the selection of polymers with different functional properties, the polymer concentration in the solutions and annealing temperatures. The particle size distribution in the developed composites followed the lognormal distribution. A double-lognormal distribution was required to interpret the magnetization data of the system containing strong interparticle interactions, and to interpret the double-peak phenomenon observed in the imaginary part of the susceptibility in some nanocomposites. DC magnetization and AC susceptibility measurements were used to study the relationship between the magnetic properties .and the average particle size by studying the superparamagnetic behavior and ferrimagnetic phase transitions of (gamma)-Fe2O3 and Mn3O4 nanoparticles in the temperature range of 2 K - 300 K. The results show that the blocking temperature TB is mainly controlled by the average particle size of the nanoparticles, and increasing the average particle size results in an upward shift of the TB. One observes no frequency dependence of TB, which indicates strong interparticle interaction in the nanoparticle assembly, in agreement with the structural results. The results revealed superparamagnetic behavior in Mn3O4 nanoparticles below the ferrimagnetic Néel temperature TN, and that TB was identified by a peak in the temperature lower than the ferrimagnetic transition peak marked by TN in the AC measurement. It is found that both TB and TN of Mn3O4 depend on the average particle size, and reducing the average particle size of Mn3O4 from 3.5 nm to 2.8 run results in a shift of TB from 14 K to 7 K, and TN from 36 K to 31 K (bulk Mn3O4 TN= 42 K)
Synthesis and Characterization of Nanocomposites
Keywords: electrosynthesis; superparamagnetic film; films; nanocomposite; organic; inorganic